Validation of happiness scale convergence in santri through Multi-trait Multi-method Analysis - Marliani, Rosleny; Ramdani, Zulmi; Imran, Jam’an Muhamad Hasan (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
Happiness is a concept that is difficult to understand to this date. Differences in individual perspectives in interpreting happiness also affect the processing construct of the measurement. This study aims to conduct convergent validation of the existing happiness scale. Convergent validation can test how good the happiness scale is by comparing the externally to another scale that is considered to have a relationship. The happiness convergent-scale validation adapted the Multi-trait Multi-method (MTMM) analysis. Respondents involved in this study were 186 students from traditional Muslim schools or Santri who were selected according to the specified characteristics and studied at UIN Sunan Gunung Djati Bandung. The three measuring instruments used are the Oxford Happiness Questionnaire (OHQ), the Indigenous Happiness Scale (IHS), and the World Health Organization Quality of Life-Bref (WHOQOL-Bref). The correlation coefficient (r) shows values of 0.52 (OHQ-IHS), 0.53 (OHQ-WHOQOL-Bref), and 0.45 (IHS-WHOQOL-Bref). The result indicated that the correlation of the three scales tested has a statistically high relationship so that the three measuring instruments used have convergent validity and can be used to measure the construct of happiness.